Biological monitoring of aflatoxin (AFB1) in workers of swine and poultry production - Viegas, Susana (2012)
Although a great body of literature exists concerning the ingestion of food contaminated with aflatoxin, there are still few studies regarding mycotoxin inhalation in occupational settings. Since mycotoxins are relatively non-volatile, inhalation exposure is cause by inhalation of airborne fungal particulates or fungi-contaminated substrates that contain aflatoxin. We intend to know if there is occupational exposure to aflatoxin in Portuguese poultry and swine production. A total of 19 individuals (11 swine; 8 poultry) agreed and provided blood samples during the course of this investigation. Measurement of AFB1 was performed by ELISA. The samples were treated with pronase (Merck), wash in a Column C18 and purification was made with immunoaffinity columns (R.biopharma), specific for AFB1. It was applied statistical test (Mann-Whitney) to verified statistical difference in AFB1 results between the two settings. Results varied with concentrations from <LOD to 5.96 ng ml-1 (Poultry: <LOD – 3.67 ng ml-1; Swine: <LOD -5.96 ng ml-1. There wasn’t found statistical difference between the two occupational settings, however, results reveal a tendency for poultry workers have higher aflatoxin values, probably because poultry activities are promoter of particles exposure. Only women’s in both settings have results <LOD. These results are probably due to differences in the activities performed. Exposure to air and dust containing aflatoxin by inhalation should be consider a route of exposure in both settings.